Developing the Learning Trajectory of Grade VII SMP Students on Prism Volume Material in Problem-based Learning - Almira, Luthfi; Usodo, Budi; Kuswardi, Yemi (KnE Social Sciences, 2025)
This research aimed to produce a learning trajectory on prism volume material in problem-based learning, carried out in three stages: preparing for the experiment, designing the experiment, and retrospective analysis. The research subjects were students of class VII in two Wonogiri junior high schools. The trial of Hypothetical Learning Trajectory (HLT) for cycle 1, or the so-called pilot experiment, involved 6 students of class VII E and trial of HLT for cycle 2, or the so-called teaching experiment, involved 32 students of class VII G. The instruments for data collection were observation sheet, interview protocol, and learning video recording. The prism volume learning trajectory started from defining the prism, determining the elements of prism, grouping examples and non-examples of prism, and finding the formula for the volume of prism. The results showed that the learning trajectory can assist students in finding and developing an understanding of the prism volume formula.